Peran Kecerdasan Emosional dan Tingkat Ketergantungan Nikotin pada Niat Berhenti Merokok - Dewi Masithah; Oedojo Soedirham; Rita S. Triyoga (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Smoking cessation intention is a motivating factor that influence to smoking cessation behavior. Smokingcessation intention is influenced by attitude toward smoking cessation behavior, subjective norm, and perceivedbehavior control. This research aims to analyze the influence of emotional intelligence and nicotine dependencelevel on smoking cessation intention. This research was obesevational analytic study with cross sectional designand used a quantitative approach. The population of this study were male smoker college student of state universityin Madura. The sampling method used proportionate stratified random sampling with sample size 290 collegestudent. The result of this study are emotional intelligence influenced smoking cessation intention trough attitudetoward smoking cessation behavior and subjective norm. Nicotine dependence level influenced smoking cessationintention trough attitude toward smoking cessation, subjective norm, and perceived behavior control. The conclusionof this study was nicotine dependence level has more influence on smoking cessation intention than emotionalintelligence.